Ginkgolide B targets and inhibits creatine kinase B to regulate the CCT/TRiC-SK1 axis and exerts pro-angiogenic activity in middle cerebral artery occlusion mice. (June 2022) - Zhu, Jiale; Jin, Zhiwei; Yang, Lei; Zhao, Caili; Hu, Jianping; Chen, Jinhu; Han, Yubao; Yu, Pei; Luo, Jun; Kong, Lingyi; Zhang, Chao
Abstract: Promoting angiogenesis in the ischemic penumbra is a well-established method of ischemic stroke treatment. Ginkgolide B (GB) has long been recognized for its neuroprotective properties following stroke. As previously reported, it appears that stroke-induced neurogenesis and angiogenesis interact or are dependent on one another. Although the pharmacodynamic effect of GB on cerebral blood flow (CBF) following ischemic stroke has been reported, the molecular mechanism underlying this effect remains unknown. As such, this study sought to elucidate the pharmacodynamic effects and underlying mechanisms of GB on post-stroke angiogenesis. To begin, GB significantly increased the proliferation, migration, and tube formation capacity of mouse cerebral hemangioendothelioma cells (b.End3) and human umbilical vein endothelial cells (HUVEC). Additionally, GB significantly improved angiogenesis after oxygen-glucose deprivation/reperfusion (OGD/R) in endothelial cells. The dynamics of CBF, brain microvascular neovascularization and reconstruction, and brain endothelial tissue integrity were examined in middle cerebral artery occlusion (MCAO) mice following GB administration. Through label-free target detection techniques, we discovered for the first time that GB can specifically target Creatine Kinase B (CKB) and inhibit its enzymatic activity. Additionally, we demonstrated through network pharmacology and a series of molecular biology experiments that GB inhibited CKB and then promoted angiogenesis via the CCT/TRiC-SK1 axis. These findings shed new light on novel therapeutic strategies for neurological recovery and endothelial repair following ischemic stroke using GB therapy. Graphical Abstract: ga1 Highlights: CKB is a prospective pharmacological therapeutic target against ischemic stroke. Ginkgolide B binds to CKB and inhibits its enzymatic activity. The CCT/TRiC-SK1 axis is regulated by Ginkgolide B. CCT2 is the primary mediator of Ginkgolide B-induced angiogenesis.